Efficient Splitting Methods Based on Modified Potentials: Numerical Integration of Linear Parabolic Problems and Imaginary Time Propagation of the Schrödinger Equation (Communications in Computational Physics, 2023)
We present a new family of fourth-order splitting methods with positive coefficients especially tailored for the time integration of linear parabolic problems and,in particular, for the time dependent Schrödinger equation, both in real and imaginarytime. They are based on the use of a double commutator and a modified processor, andare more efficient than other widely used schemes found in the literature. Moreover,for certain potentials, they achieve order six. Several examples in one, two and threedimensions clearly illustrate the computational advantages of the new schemes.